Transition Metals Embedded Siloxene as Single‐Atom Catalyst for Advanced Sulfur Host in Lithium–Sulfur Batteries: A Theoretical Study - Gong, Ning; Hu, Xuewen; Fang, Tiantian; Yang, Changyu; Xie, Tianzhu; Peng, Wenchao; Li, Yang; Zhang, Fengbao; Fan, Xiaobin (Advanced energy materials, 2022)
The practical applications of lithium–sulfur batteries are presently hindered by the shuttle effect, sluggish reaction kinetics, and poor electronic conductivity of sulfur. Siloxene, a new 2D nanomaterial with three types of structures (Weiss, chain like, and Kautsky), is regarded to be a promising cathode‐supporting material for Li–S batteries. Herein, a series of 3d transition metal single‐atom embedded siloxenes (TM‐SA‐siloxenes) is designed and their potential in Li–S batteries is evaluated by first‐principles calculations. It is found that Weiss‐siloxene shows the best polysulfide anchoring ability and lowest Gibbs free energy for the sulfur reduction reaction (SRR). Among a series of TM‐SA‐siloxenes, Co‐SA‐siloxene is identified as the optimal candidate. It shows moderate adsorption energies for polysulfides and outstanding bifunctional electrocatalytic activity for SRR and Li2S decomposition, as well as excellent electronic conductivity. It is also revealed that suitable d and p band center positions, obvious hybridization between Co–3d and S–3p orbitals, and more charge obtained from adsorbed polysulfides, contribute to the high redox kinetics of Co‐SA‐siloxene for the catalyzing conversion of polysulfides. These interesting results provide valuable theoretical guidance for the study of siloxene‐based cathode host materials for Li–S batteries. Transition metal single‐atom embedded siloxene (TM‐SA‐siloxene) not only adsorb polysulfides effectively, but TM single‐atom insertion also promotes the sulfur reduction reaction and Li2S decomposition in the discharging and charging progresses, respectively. Therefore, TM‐SA‐siloxene as sulfur host material can suppress the shuttle effect, facilitate polysulfide conversion, and improve the electronic conductivity of S cathodes in Li−S batteries.